Reminiscences of a Journey to Lithuania - Mekas, Jonas (USA : Re:Voir, 1971)
Jonas Mekas developed a unique visual language of film diary using a hand-held, super8 mm camera and jump cut editing, which he used to capture personalities, loves, and lives on film. His mobile lens lends his films a great intimacy and daring. Reminiscences is an elegiac diary film documenting the return to his birthplace of Semeniškiai, Lithuania, for the first time in 1971 after twenty-seven years of life in exile. A film diary is divided into three episodes. The first part reflects Jonas Mekas of his time as emigrant in New York, after leaving the home country of Lithuania. The second part depicts his trip back, while the last is filmed during a stay in Vienna shortly afterwards. Together, it becomes a lyrical odyssey on love, loss, and memory.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films